Impact Webs: a novel conceptual modelling approach for characterising and assessing complex risks - E. Sparkes; D. Cotti; A. Valdiviezo Ajila; S. E. Werners; S. E. Werners; M. Hagenlocher (Hydrology and Earth System Sciences)
Identifying, characterising, and assessing the complex nature of risks are vital to realise the expected outcome of the Sendai Framework for Disaster Risk Reduction. Over the past two decades, the conceptualisation of risk has evolved from a hazard-centric perspective to one that integrates dynamic interactions between hazards, exposure, system vulnerabilities, and responses. This calls for a need to develop tools and methodologies that can account for such complexity in risk assessments. However, existing risk assessment approaches are hitting limits to tackle such complexity. To this end, we developed a novel complex-risk assessment methodology named Impact Webs, inspired by a conceptual risk modelling approach named Climate Impact Chains that integrates aspects of various other conceptual models used in risk assessments, such as causal loop diagrams and fuzzy cognitive mapping. Impact Webs are developed in a participatory manner with stakeholders and characterise and map interconnections between risks, their underlying hazards, risk drivers, root causes, and responses to risks, as well as direct and cascading impacts across multiple systems and at various scales. In this methodological paper, we show how we developed the Impact Web methodology, including how we derived which elements to include in the model, demonstrating the logic and visual output and listing the steps we followed for construction. As proof of concept, we present the results of a complex-risk assessment in Guayaquil, Ecuador, which investigated how COVID-19, concurrent hazards, and responses propagated risks and impacts across sectors and systems during the pandemic. Reflecting on the utility of Impact Webs, application in case studies demonstrates the methodology's usefulness for understanding complex cause–effect relationships and informing decision-making across different scales. The participatory process of developing Impact Webs with stakeholders uncovers critical elements in systems at risk, and helps to evaluate co-benefits and trade-offs of decisions by uncovering how the outcomes of disaster risk management practices affect people, organisations, and sectors differently. Offering a system-wide perspective for modelling, Impact Webs stand as a valuable methodological contribution for complex-risk assessment.